Feasibility of Exceeding 20% Efficiency for Kesterite/c-Silicon Tandem Solar Cells Using an Alternative Buffer Layer: Optical and Electrical Analysis - Naoufal Ennouhi; Safae Aazou; Abdeljalile Er-rafyg; Zakaria Laghfour; Zouheir Sekkat (Nanomaterials)
Tandem solar cells have the potential to be more efficient than the Shockley–Queisser limit imposed on single junction cells. In this study, optical and electrical modeling based on experimental data were used to investigate the possibility of boosting the performance of kesterite/c-Si tandem solar cells by inserting an alternative nontoxic TiO2 buffer layer into the kesterite top subcell. First, with SCAPS-1D simulation, we determined the data reported for the best kesterite (CZTS (Eg = 1.5 eV)) device in the experiments to be used as a simulation baseline. After obtaining metric parameters close to those reported, the influence on the optoelectronic characteristics of replacing CdS with a TiO2 buffer layer was studied and analyzed. Different top subcell absorbers (CZTS0.8Se0.2 (Eg = 1.4 eV), CZTS (Eg = 1.5 eV), CZTS (Eg = 1.6 eV), and CZT0.6Ge0.4S (Eg = 1.7 eV)) with different thicknesses were investigated under AM1.5 illumination. Then, to achieve current matching conditions, the c-Si bottom subcell, with an efficiency at the level of commercially available subcells (19%), was simulated using various top subcells transmitting light calculated using the transfer matrix method (TMM) for optical modeling. Adding TiO2 significantly enhanced the electrical and optical performance of the kesterite top subcell due to the decrease in parasitic light absorption and heterojunction interface recombination. The best tandem device with a TiO2 buffer layer for the top subcell with an optimum bandgap equal to 1.7 eV (CZT0.6Ge0.4S4) and a thickness of 0.8 µm achieved an efficiency of approximately 20%. These findings revealed that using a TiO2 buffer layer is a promising way to improve the performance of kesterite/Si tandem solar cells in the future. However, important optical and electrical breakthroughs are needed to make kesterite materials viable for tandem applications.